(untitled) (Journal of Engineering, 2009)
Fluorophosphate neodymium laser glass has been prepared by discontinuous melting technique. Special melting and casting conditions were followed to prevent devitrification of glass samples. Furnace melting followed by slow cooling resulted formation of non vitreous glass. Problems of high viscosity melt and incomplete solubility and immiscibility of glass components were encountered by adjusting composition of glass components. X-ray diffraction analysis of the prepared glass samples proved the formation of amorphous phase. The prepared Nd – fluoride glass has low refractive index which is an important parameter for high power laser application. Optical properties of Nd – fluoride glass samples were investigated. UV – visible spectra showed almost total absorbance of light at wave length below 400 nm, while in the visible range a typical spectrum of Nd3+ ions covers the entire range. Infra – red spectral properties of these samples were studied. Transmission of the glass was found to be dependent on neodymium concentration.